Effect of Tithonia diversifolia (Hemsl.) A. Gray intake on in vivo methane (CH4) emission and milk production in dual-purpose cows in the Colombian Amazonian piedmont - Rivera, Julián Esteban; Villegas, Gonzalo; Chará, Julian; Durango, Sandra G.; Romero Sánchez, Miguel Antonio; Verchot, Louis V. (Oxford University Press, 2022)
The inclusion of Tithonia diversifolia in pasture-based diets is a promising alternative to increase bovine productivity, due to its chemical compo sition and wide adaptation, but there are few in vivo studies to determine its effect on methane yield and animal production in grazing systems. The objective of this study was to determine the effects of the T. diversifolia inclusion in a basal diet of Brachiaria humidicola on methane (CH4) emissions by enteric fermentation, and on milk yield and quality in dual-purpose cows. The polytunnel technique was used for the determination of methane yield and two diets were evaluated (Diet 1: Brachiaria humidicola 100%; Diet 2: T. diversifolia 15% + B. humidicola 85% dry matter basis) in the moderate rainy and rainy seasons using a cross-over experimental design; milk production was measured by daily milk weighing, and milk quality was determined using a LACTOSCAN analyzer. The inclusion of T. diversifolia did not increase the dry matter intake (P = 0.369), but increased the intake of crude protein and minerals, and reduced fiber intake, resulting in the increased yield of milk and its components in the moderate rainy season (P = 0.012). The inclusion of T. diversifolia reduced the absolute CH4 emissions (P = 0.016), Ym and emission intensity (per unit of fat, protein and kilogram fat and protein corrected milk yields) both in the moderate rainy and rainy seasons (P < 0.05). We conclude that the inclusion of T. diversifolia in the forage feed base in the humid tropics such as the Amazon piedmont can be used as a tool to both mitigate enteric CH4 emissions and to increase animal productivity and hence reduce emissions intensity, and thus reduce pressure on the agricultural frontier in critical areas such as the Amazon.